The reality bug - MacHale, D. J. (New York : Aladdin Paperbacks, 2003)
In his pursuit of the evil Saint Dane, Bobby finds himself on the planet Veelox, whose inhabitants have retired to their own dream worlds.
Ages 10 up.
580
Accelerated Reader AR
Keywords: Adventure stories; Fantasy; Adventure and adventurers -- Fiction; Virtual reality -- Fiction; Science fiction